A laboratory exploration for multi-period perishable food pricing. Issue 9 (7th September 2015) - Wang, Xiaohuan; Fan, Zhi-Ping; Wang, Yiming; Li, Manning
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to put forward a multi-period dynamic pricing strategy for perishable food considering consumers' price fairness perception. The impacts of the multi-period retail price, food freshness and inventory shortage risk on consumers' heterogeneous willingness to pay (WTP) and their strategic purchasing behaviours are studied. Design/methodology/approach – The authors present a price optimization model for perishable food, and conduct a laboratory experiment to justify the theoretical model. The data collected are analysed by correlation analysis and nonparametric test. Findings – The results obtained reveal, first, food freshness and inventory shortage risk have effect on consumers' heterogeneous WTP. Second, different retail prices lead to consumers' strategically purchasing behaviours. Finally, consumers' intertemporal price fairness perception and the food retailer's long-term utility maximization can be achieved by developing multi-period dynamic pricing strategy. Practical implications – This study suggests the perishable food retailer to apply a step-by-step price markdown strategy. It aims at eliminating price unfairness perceptions caused by loss of freshness and high shortage risk of the perishable food in the subsequent selling periods within the shelf life. Some valuable managerial insights towards perishable pricing for food retailers are discussed. Originality/value – This study serves as the first step to utilize a laboratory experiment to dig out consumers' intertemporal WTP towards perishable food. It also presents a novel way for describing consumers' intertemporal price fairness perception by equalizing consumers' average utilities considering consumer surplus, food freshness and shortage risk at different selling periods. The line of research on dynamic pricing concerning consumers' price fairness perception is quite new in academic research, and has arisen due to its importance for food retailers of maximizing their long-term revenues and also of constructing mutual benefit and lasting connections with the consumers.